Elites’ response to women’s action committees and local services in Nigeria - Kyle, Jordan; Adida, Claire; Arriola, Leonardo; Fisher, Rachel; Kosec, Katrina; Mo, Cecilia Hyungjung (AEA RCT Registry, 2024)
This study examines how local elites respond in the face of two interventions: a women’s training designed to strengthen women’s sense of collective efficacy and leadership skills, and a complementary training program for women’s husbands, designed to encourage and support them to become champions of women’s voice and agency. The study utilized a three-arm randomized control trial (RCT) carried out in Ogun, Osun, and Oyo states of southwest Nigeria in 2023 to analyze elite responsiveness to hypothetical petitions presented by both women and men on key community development issues. Our first intervention (treatment group 1 (T1)), the women’s training intervention, provided intensive instruction in leadership, organizing, and advocacy. It was designed to reduce psychological barriers to women’s political participation by raising women’s sense of collective efficacy and conferring skills to help women overcome these barriers. This intervention was part of a coordinated set of field experiments in five countries—collectively known as Metaketa V. Our second intervention (T2), the men’s training intervention, emphasized the benefits of women’s political participation for families and communities and focused on equipping men to be advocates for women’s empowerment and gender equality in public spaces—underscoring that women’s empowerment is not a zero-sum game.